Formulasi dan Evaluasi Sifat Fisik Sediaan Lulur Ekstrak Etanol Kulit Pisang Kepok (Musa paradisiaca L) - Yuliana, Tri Puspita; Zulda, Nurul Fitri Erlinda (Universitas Hamzanwadi, 2024)
Banana peel is the part of the banana that has not been used. A body scrub is a semi-solid preparation that functions to clean dirt on the face and dead skin cells. Banana peel one of any plants can be used as the basic of formulated cream cosmetics has flavonoid and tanin compound content, in acts as an moisturizer skin. This research aims to determine the formulation and evaluation of the physical preparation of kepok banana peel (Musa Paradisiaca L) ethanol extract scrub. The research method used was the laboratory experimental method. Evaluation of the scrub preparation includes organoleptic testing, homogeneity, spreadability testing, adhesion testing, pH testing and skin moisturizing power testing. The results showed that the preparation of the ethanol extract of kepok banana peel from both formulas had organoleptic results of F1 (semi-solid cream form, light brown color, typical aroma of kepok banana peel extract), F2 (semi-solid cream form, dark brown color, typical aroma of peel extract banana kepok), the homogeneity test of the preparation produces an even preparation when smeared on the surface of a glass object in all formulas, testing acidity or pH F1: 5.45 and F2 = 6.42. The spreading ability test results were at F1: 5.80 cm and F2: 5.44 cm. Testing ability of sticking time F1: 2.44 seconds and F2: 2.57 seconds. The skin moisturizing ability test before application showed an average of 23.6%, on day 5 an average of 36.5% and on day 10 an average of 48.5%. The conclusion is that the Kapok banana peel scrub formulation has physical properties that meet standards and is able to significantly moisturize the skin after 10 days of use. Statistical data shows that there is no significant difference in each formula with significance values ​​of 0.327, 0.265 and 0.294 (P<0.05).